Anticoagulants in Children with Renal Impairment: A Narrative Review - Kiskaddon, Amy L.; Witt, Daniel M.; Betensky, Marisol; Sochet, Anthony A.; Memken, Amanda; Male, Christoph; Goldenberg, Neil A. (Seminars in Thrombosis and Hemostasis, 2025)
Venous thromboembolism is a common cause of morbidity and mortality in children with renal disease. To properly treat and prevent thromboembolism in this patient population, it is important to be familiar with the multitude of anticoagulant agents currently available. Many anticoagulant drugs undergo some extent of renal elimination. There are important considerations for the selection, dosing, and monitoring of anticoagulant drugs for patients with renal impairment due to various pharmacokinetic alterations that may occur. While there are data to help guide dosing and monitoring in adults, evidence regarding renal dose adjustment of many anticoagulant drugs in children are limited. For the clinician, anticoagulation management in children with renal impairment presents unique challenges. In addition to considering overall bleeding risk, the extent of renal impairment may vary by patient, making a one-size-fits-all approach to managing these patients difficult. These factors, combined with limited data, can make managing anticoagulation in children with renal impairment a challenge. Therefore, the focus of this review will be to describe the pharmacokinetics of the following anticoagulants in children with impaired renal function: unfractionated heparin, enoxaparin, dalteparin, rivaroxaban, apixaban, edoxaban, fondaparinux, bivalirudin, argatroban, dabigatran, and warfarin.
Keywords: anticoagulants; pediatric; renal impairment